O capital de risco no financiamento da inovação: experiência internacional - Périco, Ana Elisa; Rebelatto, Daisy A. N. (Revista Gestão da Produção Operações e Sistemas, 2006)
The current “open market” context represents a great challenge for developing countries. The genesis of the Brazilian industry was characterized by several factors, which did not encourage the technology production in the country, such as the import substitution process, research capacity concentrated in the universities and the fact that the Brazilian companies face uncertainty as one of the greatest obstacles when investing in ReD. From this scenario, the aim of this paper is to identify ways of financing the technological development, based on successful experiences from the European Union, for example, which could be adapted to the Brazilian reality. One of the measures that could be adapted is the financing to the innovation using risk capital, with the participation of private investors. Also, the public sector could be encouraged, through temporal participation in the capital of the companies. In relation to Brazil, the participation of risk capital investors could mean a better interaction between companies and universities. In this sense, the risk capital would contribute to the company’s growth and development, and would simultaneously promote research to the development of technologies and innovations. Keywords: Technological development; Risk capital; Competitivity.